UiTM Sarawak ladies' staff volleyball team participated in 'Liga Sukan untuk Semua' (LiSUS) - Sim, Sandra Phek Lin (UiTM Sarawak, 2016)
UiTM Sarawak Ladies' Staff Volleyball Team participated in 'Liga Sukan untuk Semua' (LiSUS) at the Samarahan Division Level on 5th and 6th of September 2015. The tournament was jointly organised by the Youth and Sports' Association (Kesatuan Belia dan Sukan) and UiTM Sarawak. Five teams participated in the ladies' volleyball competition. This volleyball tournament was held for the first time in Samarahan Division. The ladies' teams that participated in this tournament were Challengers (UiTM Sarawak Ladies' Staff team), Forza, IPG KTAR, UiTM (UiTM students' team) and IPD.